Japan : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
The new government in Tokyo has a window of opportunity to address the deep-seated structural problems that lie at the root of Japan's lackluster economic performance over the past decade. The government has appropriately identified banking sector problems as a top priority. Broader reforms are needed to strengthen the regulatory framework and lay the basis for a sound banking system. In the near term, fiscal policy should remain responsive to changing economic circumstances. Enhancing the transparency of the monetary policy framework is required.